Letter : Adoption of a Spanish Child - Chester, George
1939-03-02 038-0100-001 NATIONAL UNION OF BOOT & SHOE OPERATIVES Affiliated to the English, Irish & Scottish Trades Union Congresses & National Labour Party. Approved under the National Health Insurance Acts Approval No 281 and the Unemployment Insurance Acts Code No 245 GENERAL PRESIDENT LEN. SMITH GENERAL SECRETARY GEO. CHESTER 28, BEDFORD SQUARE LONDON, W.C.1 Telephone: MUSEUM 4438 Telegrams: NATUNISHOP PHONE LONDON GC/S. IND. March 2nd, 1939. Mr. H.V. Tewson, Trades Union Congress. Dear Mr. Tewson, Adoption of a Spanish Child. I am more than grateful to you for your letter of yesterday's date in response to my telephone enquiry of Monday last. The official in question will be in this office tomorrow, when I will hand to him your letter, and discuss further with him the request he has made. It is noted, however, that you will make enquiries with regard to the possibility, and get into touch with me again later. With many thanks for your kind assistance in this matter. Faithfully yours, Geo Chester General Secretary. 292/946/38/100(I)